Insights into the thermoelectric properties of the Cu2Ge(S1-xSex)3 solid solutions. (2017) - Jacob, Stéphane; Delatouche, Bruno; Péré, Daniel; Jacob, Alain; Chmielowski, Radoslaw
Abstract: Although the crystal structure of Cu2 Ge(S1-x Sex )3 with 0 < x < 1 has been recently reported by several authors, the dependence of the thermoelectric properties of these compounds as a function of x has not been published yet. In this work, we have employed ampoule synthesis followed by Spark Plasma Sintering (SPS) in order to prepare samples of Cu2 Ge(S1-x Sex )3 covering the whole range of x . Each specific stoichiometry has been characterized by XRD, Hall effect measurements at room temperature, and power factor measurements versus temperature. Moreover, we have measured the thermal diffusivity and the heat capacitance versus temperature for each cases in order to quantify their respective thermoelectric figure-of-merit ( zT ). All samples have been found to exhibit a p-type conductivity as attested by Hall effect measurements. Among the different compounds investigated, Cu2 GeSe3 ( x = 1) has shown the highest thermoelectric performance with a zT of 0.31 at a temperature of 730K. This zT could be increased up to 0.42 at the same temperature by using an excess of germanium. In the case of Cu2 GeS3 ( x = 0), a decrease of the resistivity by 3 orders of magnitude could be achieved by an adequate doping with indium. We thereby report the first zT values ever published on p-type doped Cu2 GeS3 .